Implementation of Building Construction Prohibition In Watershed (Case Study on Brantas Watershed in Soekarno-Hatta Area, Malang) - Vega Alif Wijaya (Faculty of Law, Merdeka University Surabaya, 2018)
The objective of research was aims to find, analyze and understand the policy implementation of the ban on construction of building in watershed (DAS Brantas Case Study on Region Soekarno-Hatta Malang). The legal analysis is focused in finding the limiting factors in the enforcement of the ban on construction of the building in the watershed, the legal consequences of the construction of the building in the watershed area and the efforts to enforce the provisions on the prohibition of building in the watershed. The journal is prepared by the method of empirical juridical approach sociological jurisdiction. Based on the survey results revealed that basically factors which hinder the enforcement of the ban on construction of the building in the watershed occurs because Due to the lack of public awareness regarding the building was required to have a permit, factors of weak local economy, the law enforcement officers who are not firmly against the demolition in the area of watershed Brantas also because of the buildings that have stood prior to Regulation No. 1 Year 2012 Malang. The legal consequences of the construction of the building in the watershed area, namely a written warning and a call to the offenders concerned. While efforts to enforce the provisions of the ban on building in the watershed of them with socialization related rules and if there is a violation, the violator will be called to give advance warning letter, if it is still in violation will be given sanction by misdemeanor.